Immune responses against hepatitis C virus genotype 3a virus-like particles in mice: A novel VLP prime-adenovirus boost strategy. Issue 8 (17th February 2016) - Kumar, Anuj; Das, Soma; Mullick, Ranajoy; Lahiri, Priyanka; Tatineni, Ranjitha; Goswami, Debashree; Bhat, Prasanna; Torresi, Joseph; Gowans, Eric James; Karande, Anjali Anoop; Das, Saumitra
Highlights: Generated VLP based vaccine against HCV genotype-3a and 1b. Novel heterologous prime boost strategy eliciting high antibody and T cell response. Combined regimen of VLP followed by recombinant adenovirus could more effectively inhibit HCV infection. Abstract: Chronic hepatitis C virus (HCV) infection represents a major health threat to global population. In India, approximately 15–20% of cases of chronic liver diseases are caused by HCV infection. Although, new drug treatments hold great promise for HCV eradication in infected individuals, the treatments are highly expensive. A vaccine for preventing or treating HCV infection would be of great value, particularly in developing countries. Several preclinical trials of virus-like particle (VLP) based vaccine strategies are in progress throughout the world. Previously, using baculovirus based system, we have reported the production of hepatitis C virus-like particles (HCV-LPs) encoding structural proteins for genotype 3a, which is prevalent in India. In the present study, we have generated HCV-LPs using adenovirus based system and tried different immunization strategies by using combinations of both kinds of HCV-LPs with other genotype 3a-based immunogens. HCV-LPs and peptides based ELISAs were used to evaluate antibody responses generated by these combinations. Cell-mediated immune responses were measured by using T-cell proliferation assay and intracellular cytokine staining. We observed that administration of recombinant adenoviruses expressing HCV structural proteins as final booster enhances both antibody as well as T-cell responses. Additionally, reduction of binding of VLP and JFH1 virus to human hepatocellular carcinoma cells demonstrated the presence of neutralizing antibodies in immunized sera. Taken together, our results suggest that the combined regimen of VLP followed by recombinant adenovirus could more effectively inhibit HCV infection, endorsing the novel vaccine strategy.